Acculturative Stress and Risky Sexual Behavior: The Roles of Sexual Compulsivity and Negative Affect. (January 2016) - Jardin, Charles; Garey, Lorra; Sharp, Carla; Zvolensky, Michael J.
Recent syndemic models of sexual health disparities affecting racial/ethnic minorities have highlighted the role of discrimination. Yet no previous work has examined how acculturative stress (distress at the transition from one's original culture toward a new culture) associates with sexual HIV-risk behavior (SHRB). Work among other minority populations suggests sexual compulsivity (SC) may contribute to syndemic sexual health disparities as a means of coping with distress. With this in mind, the present study examined whether SC explained the relation between acculturative stress and SHRB. Separate analyses were conducted for males and females within a sample of 758 sexually initiated racial/ethnic minority college students. Among males and females, acculturative stress had an indirect effect on SHRB via SC. As the first study to examine SHRB in relation to acculturative stress, findings provide preliminary evidence that targeting SC among racial/ethnic minorities may help reduce sexual health disparities.